Dom Helder: um sopro progressista na Arquidiocese de Olinda e Recife - Silva, Severino Vicente da (Revista eclesiástica brasileira, 2002)
This study proposes to discuss and challenge some of the statements defending the hypothesis that the Archdiocese of Olinda and Recife – the Catholic Christians – opted for a progressive line of action from the 60s onwards. We wish to argue that the pastorship of Dom Helder Câmara (1964-1985) at the head of the Archdiocese was a progressive interregnum that occured in a society ofa conservative nature and did not succeed in reaching the foundations of the practice of the Archdiocese's Catholics.